Penipuan Dalam Jual Beli Menurut Hadits Dan Pasal 493 Kuhp - Muhammad Satria Akbar; Tajul Arifin (Lembaga Pengembangan Kinerja Dosen, 2024)
, This research presents opinions on the theme of fraud in buying and selling based on an Islamic perspective and Indonesian positive law, with a focus on Article 493 of the Criminal Code (KUHP). In the Islamic context, honesty and fairness in buying and selling transactions are highly emphasized as an integral part of religious values. On the other hand, Article 493 of the Criminal Code regulates criminal acts of fraud in buying and selling transactions in Indonesia, providing a legal basis for handling cases of fraud in trading activities. A comparative analysis between Islamic views and Indonesian positive law towards fraud in buying and selling reveals similarities and differences in approach and implementation. The implications of these two perspectives are also discussed in the context of legal practice in society.